The Good Quality of Life of Breast Carcinoma with Aggressive Metastasis to Multilevel Vertebrae: A Case Report - Mannagalli, Yusuf; Kirana, Ignatia Rosalia; Niatazya, Arindita; Utami, Lusyhandri Wiga; Pratiwi, Dwirani Rosmala (http://dharmais.co.id/, 2024)
Introduction: Bone is one of the most common metastase sites in breast cancer after lung and liver. Spinal involvement is regarded as an aggressive form of bone metastases due to the risk of neurological dysfunction and paralysis resulting in pain and disability. Therefore, the presence of spinal metastases in breast cancer usually worsens the quality of life (QoL) of patients. This is a persisting challenge in palliative care which aims to improve QoL and provide pain relief. In this case, we reported a 56-year-old female with end-stage breast cancer and extensive spinal involvement who had good QoL based on subjective and objective assessment. Case Presentation: A 56-year-old patient complained of pain in the left breast and back. Physical, imaging, and histopathology examination concluded that the patient suffered from stage IV breast cancer spreading to cervical and lumbal vertebrae, however, the patient reported minimal disturbances in daily activity despite the pain. Objective assessment of quality of life was done using EORTC QLQ-C30, QLQ-BM22, and QLQ-BR23, which revealed a high level of global health status exceeding average breast cancer patients. The high QoL observed in our patient could be attributed to effective symptom management, strong social support, and resilience in coping with the challenges of breast cancer. Conclusions: Continuous psychosocial support, effective symptom management, and strengthening individual resilience have the potential to improve the quality of life in breast cancer patients with spinal metastases.